2016
DOI: 10.1189/jlb.3ma0915-418r
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor drives neutrophil accumulation by facilitating IL-1β production in a murine model of acute gout

Abstract: This study evaluated the role of macrophage migration inhibitory factor in inflammation caused by monosodium urate crystals. The concentration of macrophage migration inhibitory factor was increased in synovial fluid of patients with acute gout, and there was a positive correlation between intra-articular macrophage migration inhibitory factor and IL-1β concentrations. In mice, the injection of monosodium urate crystals into the knee joint increased the levels of macrophage migration inhibitory factor in macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 43 publications
2
26
1
Order By: Relevance
“…In another treatment test, mice were divided into two groups, receiving vehicle and reparixin, respectively after administration of bleomycin plus PM. Reparixin treatment protocol referred to that described in previous research [32][33][34]. The treatment group received subcutaneous injection of reparixin (30 mg/kg in 100 µL saline-diluted DMSO) (Tocris, Bristol, U.K.) at 30 min before administration of bleomycin and PM, followed by maintenance dose (30 mg/kg in 100 µL saline-diluted DMSO) from day 0 to day 2.…”
Section: Animal Modelsmentioning
confidence: 99%
“…In another treatment test, mice were divided into two groups, receiving vehicle and reparixin, respectively after administration of bleomycin plus PM. Reparixin treatment protocol referred to that described in previous research [32][33][34]. The treatment group received subcutaneous injection of reparixin (30 mg/kg in 100 µL saline-diluted DMSO) (Tocris, Bristol, U.K.) at 30 min before administration of bleomycin and PM, followed by maintenance dose (30 mg/kg in 100 µL saline-diluted DMSO) from day 0 to day 2.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Thus, understanding how inflammasome activation is regulated is critical for the development of better treatment strategies. Significantly, one study has demonstrated that MIF is required for IL-1β release and neutrophil recruitment in a mouse model of monosodium urate (MSU) crystal-induced gout 36 , suggesting a possible function of MIF in the regulation of IL-1 in the specific context of NLRP3 activation.…”
Section: Introductionmentioning
confidence: 99%
“…Gouty arthritis is characterized by increased hyperuricemia level, which is triggered by disorders of the purine catabolic pathway, and leads to the deposition of monosodium urate (MSU) crystals within synovial joints and tissues. 1 This process of an acute inflammatory attack with intense pain, swelling and skin reddening is highlighted by the influx of neutrophils into articular or periarticular tissues and the release of inflammatory cytokines after the phagocytosis of deposited MSU microcrystals and membranolysis by monocyte–macrophages, 2 which further magnifies the inflammation cascade. The resultant stimulation of inflammatory cytokines is a cardiovascular risk factor, 3 which contributes to the significant damage against human umbilical vein endothelial cells (HUVECs) via an increased apoptosis rate 4 and thrombus formation.…”
mentioning
confidence: 99%